The Evolution of Military and Non-Military Means in Russian Strategic Thinking - Damir Sedrayev (Slovo, 2022)
This article discusses how Russian strategic thinking has evolved from the dissolution of the Soviet Union to the present day. Special emphasis will be placed on non-military means and how their presence has evolved over time. To demonstrate this, both statements and articles of the most prominent figures of the Russian theoretical field of each era will be used, up to the modifications in the national security documents issued by the Russian Federation. As we will see, the role of non-military means has undergone major changes since the birth of the contemporary Russian state in 1991.
Keywords: Non-military means; Military means; Hybrid Warfare; Non-Contact Warfare; Gareyev; Gerasimov; Adaptative Aproach to the use of force